Multifaceted Bioanalytical Methods for the Comprehensive Pharmacokinetic and Catabolic Assessment of MEDI3726, an Anti-Prostate-Specific Membrane Antigen Pyrrolobenzodiazepine Antibody–Drug Conjugate - Huang, Yue; Del Nagro, Christopher J; Balic, Kemal; Ismaiel, Omnia A; Ma, Eric; Faria, Morse; Wheeler, Aaron M; Yuan, Moucun; Waldron, Michael P; Peay, Marlking G; Cortes, Diego F; Roskos, Lorin; et al. (Analytical chemistry (Washington), 2020)
Complex biotherapeutic modalities, such as antibody-drug conjugates (ADC), present significant challenges for the comprehensive bioanalytical characterization of their pharmacokinetics (PK) and catabolism in both preclinical and clinical settings. Thus, the bioanalytical strategy for ADCs must be designed to address the specific structural elements of the protein scaffold, linker, and warhead. A typical bioanalytical strategy for ADCs involves quantification of the Total ADC, Total IgG, and Free Warhead concentrations. Herein, we present bioanalytical characterization of the PK and catabolism of a novel ADC. MEDI3726 targets prostate-specific membrane antigen (PMSA) and is comprised of a humanized IgG1 antibody site-specifically conjugated to tesirine (SG3249). The MEDI3726 protein scaffold lacks interchain disulfide bonds and has an average drug to antibody ratio (DAR) of 2. Based on the structural characteristics of MEDI3726, an array of 4 bioanalytical assays detecting 6 different surrogate analyte classes representing at least 14 unique species was developed, validated, and employed in support of a first-in-human clinical trial (NCT02991911). MEDI3726 requires the combination of heavy-light chain structure and conjugated warhead to selectively deliver the warhead to the target cells. Therefore, both heavy-light chain dissociation and the deconjugation of the warhead will affect the activity of MEDI3726. The concentration–time profiles of subjects dosed with MEDI3726 revealed catabolism of the protein scaffold manifested by the more rapid clearance of the Active ADC, while exhibiting minimal deconjugation of the pyrrolobenzodiazepine (PBD) warhead (SG3199).